Pengurusan Sertifikat Minimum Safe Manning MT. Mumbai melalui Aplikasi SIMKAPEL oleh PT. Multi Jaya Samudera Belawan - Putri Amanda; Dirhamsyah Dirhamsyah; Eka Fransiska (Jurnal Transformasi Bisnis Digital, 2025)
Under the umbrella of PT. Waruna Nusa Sentana Group, PT. Multi Jaya Samudera Belawan operates in the shipping and ship agency services sectors. The aim of this paper is to analyze the management of the Minimum Safe Manning Certificate (MSM) for the MT. Mumbai vessel through the SIMKAPEL application by PT. Multi Jaya Samudera Belawan. This certificate is crucial as it determines the minimum number and qualifications of crew members required to comply with international safety regulations. This study uses two methods: field research, which involves direct observation of the administrative process, and library research, which reviews relevant literature and regulations. The results of the study show that the use of the SIMKAPEL application accelerates the document processing, improves data accuracy, and reduces administrative errors. The implementation of this digital system also enhances service transparency and facilitates system integration. Overall, SIMKAPEL has proven to be effective in streamlining the issuance of the Minimum Safe Manning Certificate and ensuring the MT. Mumbai vessel's operational compliance with maritime safety standards. Thus, SIMKAPEL plays a vital role in supporting administrative efficiency and operational safety of the vessel.